ANTIMICROBIAL ACTIVITIES OF SOME SAUDI ARABIAN HERBAL PLANTS - Shahat, Abdelaaty A.; Mahmoud, Elsayed A.; Al-Mishari, Abdullah A.; Alsaid, Mansour S. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Several edible plants are used in Kingdom of Saudi Arabia since early time to control microbial infections. In the present study, twenty-four Saudi Arabian medicinal plants d according to traditionally used were select and investigated for the antimicrobial activities Materials and Methods: This study was designed at evaluating the antimicrobial activities of the methanol extracts of twenty-four species of sixteen plant families used in the traditional medicine by Saudi Arabian people for the treatment of numerous ailments of the microbial and non-microbial origin against four Gram-positive, four Gram-negative bacteria and four fungi and yeast using the agar well diffusion method. Results: Of most of the plants tested were found to be active against two to eight organisms. Five plants were active against eight organisms. The data appeared that extracts of Echium arabicum (SY-176), Rhantarium epapposum (SY- 180), Rumex vesicarus (SY-181), Ziziphus nummularia (SY-188), Caylusea hexagyna (SY-197) and Artemisia monosperma (SY-198) have anti-microbial activity against the most of tested bacteria, fungi and yeast. Whereas (SY- 181), the extracts of Teucrium oliverianum (SY-175), Zilla spinosa (SY-187), and Rhazya stricta (SY-195) have poor action against the tested bacteria, fungi and yeast. Conclusion: The antimicrobial activity of plant extracts against bacteria was more effective than against fungi